Discretionary Expenditures and Profit Risk Management: The Galbraith-Caves Hypothesis - Christofides, Louis N.; Tapon, Francis (Quarterly Journal of Economics, 1979)
I. Introduction, 303.—II. Model and comparative static properties, 306.—III. The influence of market power on equilibrium per unit discretionary expenditures, 312.—IV. Concluding remarks, 314.—Mathematical appendix, 315.